Porous membrane composites with cross-linked fluorinated ionic polymers
By forming a crosslinked fluorinated ionic polymer coating on the microporous membrane, the dehumidification problem caused by gas accumulation during the filtration process of the hydrophobic microporous membrane is solved, and non-dehumidification using methanol and aqueous solution is achieved. Wet properties improve fluidity and filtration efficiency and reduce the environmental impact of the wetting process.
Patent Information
- Application Number
- CN202380041424.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-19
- Publication Date
- 2024-12-31
AI Technical Summary
The existing hydrophobic microporous membranes are prone to dehumidification due to gas accumulation during the filtration process, reducing the filtration area, and the wetting process is time-consuming, water-consuming and environmentally friendly, making it difficult to ensure full penetration of the holes.
Using a crosslinked fluorinated ionic polymer coating, coated by a liquid coating composition and exposed to electromagnetic radiation, it forms a crosslinked fluorinated ionic polymer on the microporous membrane support, forming non-dewetting micropores The membrane complex can be wetted with a solution containing methanol and water.
The non-dewetting characteristics of the microporous membrane are achieved, the fluidity and filtration efficiency are improved, the use of solvents and water during the wetting process is reduced, and the risk of membrane rupture caused by high-temperature crosslinking is avoided.
Smart Images

Figure CN119234014A_ABST
Abstract
Description
Technical Field
[0001] The field of the disclosure is filters and filter membrane composites containing cross-linked fluorinated ionomers on the surface of a microporous membrane support and related methods. Background Art
[0002] Filter membranes made from porous polymer materials are used in a variety of filtration applications, including for filtering liquids and gases.
[0003] In the manufacture of microelectronic circuits, filter membranes made of polymer pore membranes can be used to purify various chemically active liquid or gaseous fluids to remove particle contamination from the fluids. Suitable polymer membranes are chemically resistant to the fluids passing through the membranes.
[0004] In general, hydrophobic hole filter membrane is not easy to wet with water. During the filtering operation, filtering the liquid that can "exhaust" (generate gas) can cause a certain amount of gas to be released from the liquid in the filter device at the surface of the filter membrane. Hydrophobic membrane will have a greater affinity for gas than liquid. The gas coming out of the liquid can accumulate and form an air bag that adheres to the surface and hole of the hydrophobic hole membrane. As these air bags become larger in size due to continuous liquid discharge gas, the air bag begins to replace the liquid from the hole of the hydrophobic hole membrane, thereby continuously reducing the effective filtration area of the hydrophobic hole membrane. This phenomenon is generally referred to as the dehumidification of the hydrophobic hole membrane, and the fluid wetting (fluid filling) part of the hydrophobic hole membrane is gradually replaced by the non-wetting or gas filling part of the fluid. When the dehumidification of the membrane occurs, the filtration stops.
[0005] Fluoropolymers can have good chemical stability, i.e. can be chemically inert. But fluoropolymers are generally hydrophobic and difficult to wet. To wet the hydrophobic film with water or aqueous fluid, a specific operating procedure is required. Low surface tension organic solvents (e.g. isopropanol) can be used to wet the film first, then the film is contacted with a mixture of water and organic solvent, then the film is contacted with water or aqueous fluid. The process can produce a large amount of solvent waste and consume a large amount of water. Alternatively, the hydrophobic film can be wetted with water under pressure. The technology of using pressure intrusion is time-consuming and expensive, may not work for dense pore membranes, and may cause thinner film rupture. In addition, this process can not ensure that the major part of the holes in the film is fully infiltrated by water.
[0006] Compared with hydrophobic porous membranes, hydrophilic porous membranes wet spontaneously after contact with aqueous liquids, so no specific treatment of the membrane is required to wet the membrane before use. Advantageously, hydrophilic membranes can be used to treat aqueous liquids without pre-use treatment with organic solvents or pressure intrusion. Summary of the invention
[0007] There is an ongoing need for microporous membranes with improved non-dewetting characteristics that are wettable by aqueous solutions and have good flow characteristics.
[0008] The following relates to a microporous membrane composite, which includes a microporous membrane support and a coating on the surface of the microporous membrane support, wherein the coating includes a fluorinated ionomer. The fluorinated ionomer may be cross-linked, may contain hydrophilic groups, may be non-dewetting, and may be wetted with a solution containing a certain amount of methanol and water.
[0009] Crosslinked fluorinated ionomers can be formed on a microporous membrane support from a coating composition containing various monomers, oligomers, prepolymers, etc. that can react to form fluorinated ionomers, optionally including fluorinated ionomer precursors derived from the monomers. Monomers that can react to produce fluorinated ionomers ("monomer units") include: i) one or more fluorinated monomers having a fluorinated group and a reactive olefinic (unsaturated) group; ii) fluorinated monomers containing reactive olefinic (unsaturated) groups and functional groups that can be converted into hydrophilic groups; iii) a diene crosslinker; and iv) a fluorinated monomer including a reactive (e.g., olefinic) group and a terminal iodine atom or a terminal bromine atom. Although the coating composition can include a free radical initiator, a free radical initiator is not required.
[0010] According to an exemplary method, a microporous membrane composite can be prepared by applying a liquid coating composition to a microporous membrane support and exposing the coating composition to electromagnetic radiation (e.g., ultraviolet radiation) to produce a crosslinked fluorinated ionomer on the support. An exemplary process involves applying the coating composition to the membrane, followed by causing the fluorinated ionomer to become crosslinked by exposing the fluorinated ionomer to electromagnetic radiation.
[0011] The exemplary process can be carried out at non-high temperature (e.g., ambient temperature) without requiring the presence of a high crosslinking temperature and free radical initiator as required by a heat-induced crosslinking system. Compared to heat-induced crosslinking techniques, the temperature requirements of the process are lower, the microporous membrane support material does not need to withstand exposure to a higher crosslinking temperature, and the polymeric membrane support can be selected from a wider range of materials, including polymeric membrane supports that are unstable at the higher crosslinking temperatures required for heat-induced crosslinking.
[0012] The combined operations of applying the coating composition to the support and exposing the coating composition to electromagnetic radiation can be performed in a continuous manner by continuously applying the coating composition to a moving plate or "web" of a microporous membrane support, followed by continuously exposing the moving plate or web of the moving membrane support to electromagnetic radiation.
[0013] In one aspect, the present disclosure relates to a method for preparing a microporous membrane composite, the microporous membrane composite comprising a microporous membrane support and a cross-linked fluorinated ion polymer coated on the surface of the microporous membrane support. The method includes coating the microporous membrane with a liquid coating composition, the liquid coating composition comprising a fluorinated solvent and a fluorinated ion polymer dissolved or dispersed therein. The fluorinated ion polymer is derived from copolymerized reactive units, the copolymerized reactive units comprising: i) a fluorinated monomer comprising a fluorinated group and ethylenic unsaturation; ii) a fluorinated monomer comprising ethylenic unsaturation and a functional group that can be converted into a hydrophilic group; iii) a fluorinated diene monomer; and iv) a fluorinated bromo-alkyl or iodo-alkyl chain transfer agent. The method also includes exposing the coated fluorinated ion polymer to electromagnetic radiation so that the reactive units react to form a cross-linked fluorinated ion polymer.
[0014] In another aspect, the present disclosure relates to a microporous membrane composite, which includes a microporous membrane support and a hydrophilic cross-linked fluorinated ion polymer coated on the surface of the microporous membrane support. The cross-linked fluorinated ion polymer includes: a fluorinated polymer backbone and a hydrophilic group connected to the fluorinated backbone; the hydrophilic group includes a group selected from -SO3H and -COOH. The cross-linked liquid coating composition does not contain a thermally activated free radical initiator. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Exemplary systems and methods for continuously coating the described microporous membrane supports are presented.
[0016] Figure 2 Schematic block diagrams showing exemplary operations of the described methods or systems.
[0017] Figure 3 Presented are data from NMR analyses of crosslinked fluorinated ionomers prepared in the presence and absence of a thermally activated free radical initiator.
[0018] Figure 4 A calibration curve showing the absorbance of a methylene blue dye solution used in a dye binding test of a pore membrane complex according to an embodiment of the present invention is shown.
[0019] All drawings are not drawn to scale. DETAILED DESCRIPTION
[0020] The following embodiments relate to microporous membrane composites comprising a microporous membrane support and a coating on a surface of the microporous membrane support, wherein the coating comprises a fluorinated ionomer. The embodiments also relate to methods of making such microporous membrane composites.
[0021] The microporous membrane composite can be prepared by applying a liquid coating composition to a microporous membrane support and treating the coating composition to produce the desired cross-linked fluorinated ionomer on the support surface. The coating composition applied to the support contains a fluorinated ionomer, which can be partially cross-linked, i.e., incompletely cross-linked, and can be further cross-linked (i.e., "completely cross-linked") by exposing the fluorinated ionomer to electromagnetic radiation. After the fluorinated ionomer is fully cross-linked, the ionomer can be further chemically treated to "activate" the cross-linked fluorinated ionomer to add hydrophilic groups to the cross-linked fluorinated ionomer so that the cross-linked fluorinated ionomer becomes non-dewetting and can be wetted with a solution containing only methanol and water.
[0022] The crosslinked polymer comprises: a fluorinated polymer backbone, an iodine atom, a bromine atom or a combination thereof; and a hydrophilic group attached to the fluorinated backbone. The iodine or bromine atom is present at a position between the polymer (fluorocarbon) backbones within the polymer, i.e., the iodine or bromine atom connects one polymer backbone to another polymer backbone. The hydrophilic group may be selected from -SO3H, PO3H and -COOH groups, which are attached to the fluorocarbon backbone, and may be present as part of the crosslinked fluorinated ionomer in an equivalent weight ranging from 380 to 620 grams per equivalent of hydrophilic group.
[0023] The process involves applying a coating composition to the surface of a microporous membrane support, and causing the fluorinated ionomer to become crosslinked (e.g., further crosslinked) by exposing the fluorinated ionomer to electromagnetic radiation, optionally and preferably without exposing the fluorinated ionomer to an elevated temperature to cause the fluorinated ionomer to crosslink ("crosslinking temperature"). Past methods of placing crosslinked fluorinated ionomers on microporous membrane supports involve causing the fluorinated ionomer to become crosslinked by exposing the ionomer to a higher crosslinking temperature (which may be at least 100, 120, or 150 degrees Celsius or higher) in the presence of a thermally activated free radical initiator. In contrast, the systems and methods of the present specification are able to avoid the use of thermally activated free radical initiators and do not require exposing the fluorinated ionomer to a higher crosslinking temperature, but instead induce a crosslinking reaction of the fluorinated ionomer by exposing the fluorinated ionomer to electromagnetic radiation (e.g., ultraviolet radiation) (applied to the surface of the support), without the need for a higher crosslinking temperature.
[0024] Compared to methods of preparing chemically similar microporous membrane composites by exposing fluorinated ionomers to higher crosslinking temperatures (e.g., temperatures above 100 degrees Celsius) to cause the ionomers to become crosslinked, the methods of the present disclosure crosslink the fluorinated ionomers by exposing the ionomers to electromagnetic radiation. The use of electromagnetic radiation to crosslink does not require higher crosslinking temperatures, which allows for useful differences in methods of preparing microporous membrane composites and methods of forming filtration products containing microporous membrane composites.
[0025] The radiation-induced crosslinking mechanism can avoid the need to expose the coated membrane support to higher crosslinking temperatures. Radiation-induced crosslinking can be carried out at temperatures below 170, 150, 120 or 100 degrees Celsius. The use of higher crosslinking temperatures to crosslink the fluorinated ionomer coated on the surface of the microporous membrane support requires the microporous membrane support to have stability (not subject to degradation or melting) when exposed to higher crosslinking temperatures. The requirement for stability of the membrane support at higher crosslinking temperatures can be used for the selection of microporous membrane supports and excludes the use of microporous membrane supports that are not thermally stable at higher crosslinking temperatures (even if the support is otherwise applicable).
[0026] By using a radiation-induced cross-linking mechanism, the need for higher cross-linking temperatures is eliminated and microporous membrane supports that are not necessarily stable at higher cross-linking temperatures (e.g., temperatures equal to or exceeding 100, 120, 150, or 170 degrees Celsius) can be used to prepare microporous membrane composites. Suitable microporous membrane supports that may not be suitable for treatment with a heat-induced cross-linking mechanism but are suitable for treatment using a radiation-induced cross-linking mechanism include polyolefins (e.g., polyethylene (PE) and ultra-high molecular weight polyethylene (UHPE)), polyvinylidene fluoride (PVDF), and polyphenylene sulfone (PPSU).
[0027] As a separately applicable feature of the described system or process, the process of using radiation to crosslink the fluorinated ion polymer coated on the microporous membrane support can include continuous processing steps, including a continuous step of applying the coating composition to the microporous membrane support and a continuous step of crosslinking the fluorinated monomer in the coated coating composition by continuously exposing the support with the coated coating composition to electromagnetic radiation. The described process can include the steps of continuously applying the coating composition to the surface of the moving plate of the microporous membrane support, and then continuously exposing the moving plate of the microporous membrane support to electromagnetic radiation to crosslink the fluorinated ion polymer coated on the surface of the microporous membrane support. In contrast, a typical filtration product manufactured using thermally induced crosslinking technology performs the crosslinking step by heating the filter element after the membrane composite has been converted and assembled into a filter component (e.g., a filter element).
[0028] Crosslinked fluorinated ionomers can be formed on a microporous membrane support by applying a coating composition containing a fluorinated ionomer component to the support surface. The coating composition contains a fluorinated ionomer component, which includes monomers and can optionally include molecules containing (derived from) previously reacted monomers, such as oligomers or prepolymers derived from monomers, which can be referred to as fluorinated ionomer "precursors". Fluorinated ionomer precursors can be pre-reacted molecules formed from monomers that are partially crosslinked, incompletely crosslinked, and can be further crosslinked (i.e., "completely crosslinked") when exposed to electromagnetic radiation after the coating composition has been applied to the support surface. After the coating composition is applied to the membrane support, the coating composition is exposed to electromagnetic radiation to initiate crosslinking of the fluorinated ionomer without exposing the coating composition to high temperatures.
[0029] The terms "fluorinated" and "perfluorinated" are used herein in a manner consistent with the meaning of these terms in the field of chemistry and chemical coatings. Fluorinated compounds include organic compounds, polymers, ionomers, chain transfer agents, crosslinking agents, solvents, etc., which have at least one carbon-bonded hydrogen atom replaced by a carbon-bonded fluorine atom. Fluorinated compounds include perfluorinated compounds. Perfluorinated compounds or perfluorocarbon compounds are chemical compounds, including polymers, ionomers, crosslinking groups, chain transfer agents, and the like, which have all or substantially all carbon-bonded hydrogen atoms replaced by carbon-bonded fluorine atoms. Some residual hydrogen atoms can be present in the perfluorinated composition, for example, less than 2 weight percent of the perfluorinated product, and in some cases, less than 0.5 or less than 0.25 weight percent of the perfluorinated product.
[0030] The coating composition contains chemical components that can be used to produce fluorinated ionomers, wherein the components are suspended, dispersed or dissolved in a liquid medium including an organic solvent. The components include reactive units, such as monomers, crosslinkers, oligomers, chain transfer agents, etc., which can optionally react with a fluorinated ionomer "precursor" formed from monomers to form a fluorinated ionomer. In some examples, the components can be mainly or completely unreacted, such as mainly or completely reactive monomer (including crosslinker) compounds. In other examples, the components can contain reactive monomers and crosslinker compounds and a certain amount of partially reacted or partially crosslinked components that have reacted to form fluorinated ionomers (i.e., "precursors"), and the partially reacted or partially crosslinked components can be further crosslinked (e.g., become "fully crosslinked") by exposing the coating composition (and precursor) to electromagnetic radiation.
[0031] In other words, the chemical composition of the coating composition includes various combinations of monomers and optional chemical derivatives thereof as described herein, which may be completely unreacted (in monomeric form) or partially reacted to form a pre-reacted, i.e., partially polymerized or partially cross-linked, fluorinated ionomer "precursor". The ingredients including the monomers (including the cross-linking agent) and the ionomer precursor may be further reacted (i.e., cross-linked) by exposing the ingredients to electromagnetic radiation to form a "fully polymerized" fluorinated ionomer, which refers to the fluorinated ionomer after application to the microporous membrane support and after cross-linking by exposure to electromagnetic radiation. As used herein, the term "fluorinated ionomer" refers to: partially reacted (partially cross-linked) ionomers that may be present in the coating composition, as well as fully cross-linked ionomers that have been applied to the microporous membrane support as part of the coating composition and subsequently cross-linked by exposure to electromagnetic radiation.
[0032] The coating composition may contain various monomers (including crosslinkers), oligomers, prepolymers, etc. that can react to form fluorinated ionomers, optionally including fluorinated ionomer precursors derived from the monomers. The monomers that can react to produce fluorinated ionomers ("monomer units") include: i) one or more fluorinated monomers having a fluorinated group and a reactive ethylenic (unsaturated) group; ii) a fluorinated monomer containing a reactive ethylenic (unsaturated) group and a functional group that can be converted into a hydrophilic group; iii) a diene crosslinker; and iv) a fluorinated monomer including a reactive (e.g., ethylenic) group and a terminal iodine atom or a terminal bromine atom.
[0033] The fluorinated monomer (i) having a fluorinated group and an olefinic (unsaturated) group may be a fluorinated or perfluorinated monomer, examples of which include the following fluorinated unsaturated monomers: vinylidene fluoride (VDF); C2-C8 perfluoroolefins, such as polytetrafluoroethylene (TFE); C2-C8 chloro-, bromo- and iodo-fluoroolefins, such as chlorotrifluoroethylene (CTFE) and bromotrifluoroethylene; CF2=CFOR f (Per)fluoroalkyl vinyl ether (PAVE), where R f is a C1-C6 (per)fluoroalkyl group, such as trifluoromethyl, bromodifluoromethyl, pentafluoropropyl; CF2=CFOX perfluoro-oxyalkyl vinyl ether, wherein X is a C1-C6 (per)fluoroalkyl group having one or more ether groups 12 Perfluoro-oxyalkyl, for example perfluoro-2-propoxy-propyl.
[0034] Suitable fluorinated monomers (ii) containing olefinic groups and functional groups that can be converted into hydrophilic groups include: -SO2F, -COOR, -COF, and combinations thereof, wherein R is a C1 to C20 alkyl group or a C6 to C20 aryl group. An example is CF2=CF-O-CF2CF2SO2F. After the monomer is formed into a fluorinated ionomer, the functional group can be converted into a hydrophilic group, such as -SO3H or -COOH. Other examples are described in U.S. Patent No. 6,354,443.
[0035] The equivalent weight of the fluorinated monomer (ii) as part of the fluorinated ionomer (fully crosslinked or partially crosslinked) can be in the range of 380 grams / equivalent (g / eq) and 620 g / eq, for example in the range of 500 to 600 g / eq or 550 to 590 g / eq.
[0036] Suitable diene crosslinking agent molecules (iii) include the following examples having formulas OF-1, OF-2 and OF-3.
[0037] The compound of formula OF-1 is represented by:
[0038]
[0039] wherein j is an integer between 2 and 10, preferably between 4 and 8, and R1, R2, R3, R4 are H, F or C1 to C5 alkyl or (per)fluoroalkyl, which may be the same as or different from each other.
[0040] The compound of formula OF-2 is represented by:
[0041]
[0042] wherein each A is independently selected from F, Cl and H; each B is independently selected from F, Cl, H and ORB, wherein RB is a branched or straight chain alkyl group, which may be partially, substantially or fully fluorinated or chlorinated; and E is a divalent group having 2 to 10 carbon atoms, which is optionally fluorinated and may include an ether bond.
[0043] The compound of formula OF-3 is represented by:
[0044]
[0045] wherein E, A and B have the same meanings as defined above; each R5, R6, R7 is independently H, F or C1-5 alkyl or (per)fluoroalkyl.
[0046] The amount of diene (iii) can be present in the mixture of ingredients used to produce the fluorinated ionomer in any suitable amount, such as an amount ranging from 0.1 to 5 weight percent diene (iii) per total weight of fluorinated ionomer ingredients (including all monomers, precursors, etc.).
[0047] Suitable bromine- and iodine-containing monomers (iii) include, for example, those of formula R f (I) x (Br) y A fluorinated chain transfer agent, wherein R f is a fluoroalkyl group or a (per)fluoroalkyl group or a (per)fluoroalkyl group having 1 to 10 carbon atoms, and wherein x and y are integers from 0 to 2, wherein 1≤x+y≤2. Examples include bromine-containing fluoroalkyl compounds and iodine-containing fluoroalkyl compounds having 1 to 10 carbon atoms, as described, for example, in U.S. Pat. No. 9,359,480.
[0048] In an exemplary system, bromine or iodine atoms may be included in an amount ranging from 0.1 to 5 weight percent per total weight of the fluorinated ionomer composition (including all monomers, precursors, etc.).
[0049] Optionally, but not required, the coating composition may further include a free radical initiator which can promote crosslinking of the fluorinated ionomer when the fluorinated ionomer is exposed to electromagnetic radiation.
[0050] Various types of free radical initiators are known to be suitable for generating free radicals in a chemical system to initiate a reaction between the reactants of the system, such as to cause crosslinking or polymerization of reactive monomers, oligomers, prepolymers, crosslinking agents, etc. Different types of free radical initiators (or free radical initiators "radical initiators") are known, which can generate one or more chemical free radicals by different activation mechanisms. Some free radical initiators are activated by exposure to heat to generate free radicals, and they are called "thermally activated initiators". Other types of free radical initiators are activated by exposure to electromagnetic radiation to generate free radicals, and they are called "radiation activated initiators".
[0051] Different thermally activated free radical initiators are known to be suitable for inducing reactions between the chemical components used to form the crosslinked fluorinated ionomers. For example, U.S. Pat. No. 9,359,480 describes dialkyl peroxide initiators that can be activated to generate free radicals when heated to a curing temperature in the range of 100 to 300 degrees Celsius. Examples identified as specific dialkyl peroxide initiators: di-tert-butyl-peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, dibenzoyl peroxide, di-tert-butyl perbenzoate, di-1,3-dimethyl-3-(tert-butylperoxy)butyl carbonate. According to the present specification, the liquid coating composition need not include a thermally activated free radical initiator, such as any of the general or specific initiators identified in the 9,359,480 patent. Alternatively, suitable or preferred liquid coating compositions and derived crosslinked fluorinated ionomers and coatings may specifically exclude these and other thermally activated free radical initiators, for example, may contain less than 0.001, 0.0005, or less than 0.0001 weight percent of these or any other thermally activated free radical initiators.
[0052] To avoid the step of heating the liquid coating composition to induce crosslinking of the coating composition, the liquid coating compositions described in the present disclosure can be cured by non-thermal activation methods, such as by exposure to radiation, such as ultraviolet radiation having a wavelength between 300 and 400 nanometers.
[0053] Optionally, but not as a requirement, the described liquid coating compositions can include a radiation activated free radical initiator. Examples include a class of compounds known as "Type I" photoinitiators and certain types of radiation sensitive salts, such as sulfites, such as sodium sulfite (Na2SO3), which generate free radicals in the presence of ultraviolet radiation energy.
[0054] Suitable radiation-sensitive initiator compounds include Type I free radical initiators and similar compounds, which are unimolecular free radical generators that decompose to form two chemical free radicals in the presence of radiation (e.g., ultraviolet radiation in the range of 300 to 400 nanometers). Exemplary Type I free radical initiators include hydroxyacetophenone (HAP) initiators and phosphine oxide (TPO) initiators. Examples of commercially available Type I UV initiators include those sold under the trademark Irgacure (e.g., Irgacure 2959, 2-hydroxy 1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone).
[0055] A free radical initiator is optionally and not required to be present in the coating composition. In coating compositions containing a radiation activated free radical initiator, the amount of radiation activated free radical initiator in the coating composition can be a suitable amount, such as an amount in the range of 0.01 to 10 weight percent, such as 0.1 to 5 weight percent, based on the total weight of the liquid coating composition. In other examples, the coating composition may not include any free radical initiator, such as the coating composition may contain less than 0.01 or 0.005 or 0.001 weight percent of any type (heat activated or radiation activated) of free radical initiator.
[0056] The coating composition containing the fluorinated ionomer component also includes a liquid medium, which includes an organic solvent (e.g., a fluorinated solvent) in which the fluorinated ionomer component is dissolved or dispersed. The fluorinated solvent (also referred to herein as a liquid fluorocarbon medium) is a fluorinated liquid chemical substance that is suitable for dissolving or dispersing the chemical components of the coating composition to form a coating composition that will wet the surface of the microporous membrane support when applied to the pore surface of the support. The solvent may include a fluorinated organic solvent and optionally one or more other fluorinated or non-fluorinated solvents in an amount effective to form a suitable coating composition.
[0057] Exemplary fluorinated solvents include, for example, comprising, consisting essentially of, or consisting of a perfluoropolyether or a mixture of two or more perfluoropolyethers. The perfluoropolyether may have the general formula F3C-O-(CF2CF(CF3)-O) n -(CF2-O) m -CF3, wherein m and n are integers, wherein n is greater than zero and m is greater than or equal to zero. Examples of such perfluoropolyethers may have a molecular weight between 300 and 600 amu and a boiling point between 20 and 150 degrees Celsius.
[0058] Other examples of suitable fluorinated solvents include, for example, comprising, consisting essentially of, or consisting of hydrogenated fluoropolyethers. Exemplary hydrogenated fluoropolyethers (HFPEs) may have the general formula R*-OR f '-R*', wherein: R* and R*' are the same or different and are selected from: -C m F 2m+1 and -C n F 2n+1-h H h A group wherein m, n are integers from 1 to 3, h is an integer equal to or greater than 1, selected so that h is less than or equal to 2n+1, provided that at least one of R* and R*' is -C as defined above n F 2n+1-h H h group; and -R f' Selected from:
[0059] (1)-(CF2O) a -(CF2CF2O) b -(CF2-(CF2) z' -CF2O) c , wherein a, b and c are integers of up to 10, preferably up to 50, and z' is an integer equal to 1 or 2, a is greater than or equal to 0, b is greater than or equal to 0, c is greater than or equal to 0, and a+b is greater than 0; preferably, each of a and b is greater than 0, and b / a is in the range of 0.1 and 10; and
[0060] (2)-(C3F6O) c' -(C2F4O) b -(CFXO) t -, wherein X is independently selected at each occurrence from -F and -CF3; b, c' and t are integers up to 10, c' is greater than 0, b is greater than or equal to 0, and t is greater than or equal to 0; preferably, b and t are greater than 0, c' / b is in the range of 0.2 and 5.0, and (c'+b) / t is in the range of 5 and 50;
[0061] (3)-(C3F6O) c' -(CFXO) t -, wherein X at each occurrence is independently selected from -F and -CF3; c' and t are integers up to 10, c' is greater than 0, t is greater than or equal to 0; preferably, t is greater than 0, and c' / b is in the range of 5 and 50.
[0062] A suitable type of fluorinated surfactant is a methoxy nonafluorobutane compound, such as: (CF3)2CFCF2-O-CH3 or CF3CF2CF2CF2-O-CH3, in some cases having a purity of at least 99 weight percent.
[0063] Examples of commercially available fluorinated solvents include: Novec TM HFE-7100 (methoxy nonafluorobutane, surface tension 13 dyne / cm, available from 3M Company), SV90 (perfluoropolyether, surface tension 16 dyne / cm available from Solvay Solexis) and other similar fluorinated low surface tension solvents, combinations of these solvents, or mixtures containing these solvents.
[0064] The coating composition can be prepared by known methods. Exemplary coating compositions contain ingredients that can be used to produce fluorinated ionomers, optional fluorinated ionomer precursors, etc., which can be in the form of colloidal particles or gel particles suspended or dispersed in a fluorinated solvent. The particles can preferably have a relatively small particle size, such as less than 600 nanometers (nm), such as less than 300 nm, less than 125 nm, less than 40 nm, or less than an average particle size of 15 or 10 nm; for example, the average particle size of the fluorinated ionomer particles in the coating composition can be in the range of 10 nanometers to 600 nanometers, such as 10 to 300 nanometers; or in the range of 10 to 100 or 10 to 40 nanometers.
[0065] Relatively small ionomer particles will reduce the chances of particles being lodged in the pores and blocking fluid flow through the pores of the microporous membrane support, which can reduce the rate of fluid flow through the pores of the membrane support (i.e., cause "flow loss") after the cross-linked fluorinated ionomer is formed on the support to form a membrane composite when the coating composition is applied to the support.
[0066] According to some examples, suitable coating compositions contain fluorinated ionomers in the form of suspended particles, wherein at least 90 weight percent of the fluorinated ionomer particles have a particle size less than 200 nanometers (nm), for example, at least 90 weight percent of the fluorinated ionomer particles have a particle size less than 125 nm, or less than 40 nm, or less than 15 nm.
[0067] The amount of the fluorinated ionomer component in the coating composition can be an amount that will effectively produce a non-dewetting microporous membrane composite (e.g., as measured by autoclave testing) when applied to a microporous membrane support and then crosslinked and activated. In addition, the amount can be effective to produce a microporous membrane composite that can be completely wetted with a solution containing methanol and water, or in some examples, only water.
[0068] In an exemplary coating composition, the amount of fluorinated ionomer component (all non-solvents, solid components, including monomers, ionomer precursors, etc.) can be in the range of 0.1 to 4 weight percent fluorinated ionomer component / total weight coating composition (e.g., ionomer component solids and solvent), such as 0.1 to 3.5 weight percent. Coating compositions containing low concentrations of fluorinated ionomer components can produce incompletely coated microporous membrane supports that will have uncoated hydrophobic areas and will not be fully wetted by solutions containing methanol and water. Coating compositions containing excessively high concentrations of fluorinated ionomer components can produce a microporous membrane composite that exhibits a reduced amount of fluid flowing through the membrane during use.
[0069] The microporous membrane support (i.e., simply referred to as "support") can be formed from a polymer that is chemically inert to the crosslinking and activation steps of the process described herein. The microporous membrane support is a porous membrane, which can also be described by terms such as superporous membranes, nanoporous membranes, and microporous membranes. These microporous membranes effectively remove undesirable particulate materials, such as gel particles, colloids, cells, poly-oligomers, etc., that are larger than the pores of the microporous membrane from the liquid feed stream, while liquid components smaller than the pores pass through the pores.
[0070] Examples of suitable microporous membrane supports that may be considered microporous, superporous, or nanoporous may have an average pore size that may be less than 10 microns, less than 5 microns, or less than 1, 0.5, 0.1, 0.05, or 0.01 microns.
[0071] The microporous membrane support can have any useful thickness, such as about 1 to 100 microns or 5 to 75 microns.
[0072] Exemplary supports can be made from fluorinated or perfluorinated, chemically inert polymers. Examples of fluorinated microporous membrane supports include polytetrafluoroethylene (PTFE), fluorinated ethylene-propylene (FEP) copolymers, copolymers of tetrafluoroethylene and perfluoropropyl vinyl ether (PFA, also known as perfluoroalkoxy polymers), copolymers of tetrafluoroethylene and perfluoromethyl vinyl ether (MFA), and polymer compositions containing any of these. The microporous membrane support can be formed, for example, from polytetrafluoroethylene, fluorinated ethylene-propylene copolymers, or perfluoroalkoxy polymers, including those manufactured by EI Dupont deNemours and Company with PTFE, FEP and PFA or amorphous form Polymers (e.g. AF polymers) designate a group of fluoropolymers (generally known as fluorocarbons) sold under the trade name fluorocarbons.
[0073] Other fluorocarbon compounds for microporous membrane supports may include, but are not limited to, for example, fluorocarbons available from Daikin Industries, Ltd. -PFA and -FEP or various grades from Solvay Solexis -PFA and -MFA. Fluoropolymers have excellent chemical and thermal resistance and are generally hydrophobic. Other suitable thermoplastic fluoropolymers that can be used may include homopolymers and copolymers comprising monomer units derived from fluorinated monomers, such as vinylidene fluoride (VF2), hexafluoropropylene (HFP), chlorotrifluoroethylene (CTFE), vinyl fluoride (VF), trifluoroethylene (TrFE) and tetrafluoroethylene (TFE), and optionally in combination with one or more other non-fluorinated monomers.
[0074] Although fluoropolymer membrane carriers are suitable for processing membrane composites at high temperatures, including by heat-induced crosslinking, the exemplary methods described in the present disclosure can be processed without being exposed to higher crosslinking temperatures, including by crosslinking. By using a crosslinking step initiated by electromagnetic radiation, the membrane carrier is not exposed to higher crosslinking temperatures, and the membrane carrier does not need to have thermal stability. Therefore, the membrane carrier can be prepared by a polymeric material that does not have to be stable to higher crosslinking temperatures, which allows the use of a membrane carrier made of polyolefins, such as polyethylene and ultra-high molecular weight polyethylene (UHPE), polyvinylidene fluoride (PVDF) and polyphenylene sulfone (PPSU).
[0075] According to the applicable method, the microporous membrane composite can be prepared by the following steps, including continuously applying the coating composition to the surface of the mobile microporous membrane support to form what is referred to as a "coated microporous membrane support" or "coated support". Subsequently, the coated support is also exposed to electromagnetic radiation in a continuous manner to crosslink the fluorinated ion polymer of the coating composition. Subsequently, the coated support after crosslinking can be treated to convert the coated support into a filter membrane for filtering a product. One or more of the subsequent processing steps can be optionally and preferably performed in a continuous manner.
[0076] In an exemplary method, after coating a microporous membrane support with a coating composition and exposing the coating composition to electromagnetic radiation to crosslink the fluorinated ionomer (i.e., "fully crosslinked"), the resulting coated support can be treated to remove excess coating composition, followed by drying the support, and then chemically converting the functional groups of the fluorinated monomer to hydrophilic groups. Specific steps (which can be in any suitable order) include: extracting excess (e.g., unreacted) components of the coating composition remaining on the surface after crosslinking to remove excess components from the coated support; drying the fully crosslinked coating after the crosslinking and extraction steps; folding or pleating the coated membrane with the fully crosslinked fluorinated ionomer to form a pleated filter membrane from the coated support; assembling a filter membrane product containing the pleated membrane; and chemically converting the functional groups of the fully crosslinked fluorinated ionomer that can be converted to hydrophilic groups to hydrophilic groups.
[0077] The conversion or "activation" of the convertible functional groups of the fluorinated ionomer into hydrophilic groups, such as the conversion of sulfonyl groups -SO2F into acid sulfonic acid groups SO3H, can be carried out by known methods. For example, the activation can be carried out by treating the intermediate coated support with the fully crosslinked ionomer in a strong base (such as KOH) aqueous solution (for example, a concentration of about 10 weight percent) for a time range of about 4 hours to about 8 hours and a temperature range of about 65 to about 85 degrees Celsius; then washing the treated coated support in demineralized or deionized water at 80 to 90 degrees Celsius for 30 minutes to remove unreacted ion membranes; treating the coated support in a strong acid (such as HCl or nitric acid) aqueous solution (for example, a concentration of about 20 weight percent) at room temperature for a time range of about 2 hours to about 16 hours; then washing the coated support with demineralized or deionized water. The chemical conversion of -COF and or -COOR groups can be carried out similarly. A microporous membrane support that has been coated with a coating composition containing a fluorinated ionomer, then fully crosslinked as described above and then activated, is referred to as a microporous membrane composite.
[0078] In useful and preferred embodiments, the fully crosslinked fluorinated ionomer of the microporous membrane composite may contain an active free radical initiator, such as included in the liquid coating composition to promote crosslinking of the fluorinated ionomer component of the liquid coating composition.
[0079] In other useful and preferred embodiments, the fully crosslinked fluorinated ionomer of the microporous membrane may not include radiation activated free radical initiators, for example, may contain less than 0.01 or 0.005 or 0.001 weight percent radiation activated free radical initiators.
[0080] In these and other useful and preferred examples, the fully crosslinked fluorinated ionomer of the microporous membrane may not include a thermally activated free radical initiator, including any of those described in U.S. Pat. No. 9,359,480, which includes a dialkyl peroxide initiator that can be activated to generate free radicals when heated to a curing temperature in the range of 100 to 300 degrees Celsius. Specific examples include dialkyl peroxides such as di-tert-butyl-peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, dibenzoyl peroxide, di-tert-butyl perbenzoate (also known as Luperox 101), di-1,3-dimethyl-3-(tert-butylperoxy)butyl carbonate. Exemplary fully crosslinked fluorinated ionomers of the microporous membrane of the present disclosure may contain less than 0.01 or 0.005 or 0.001 weight percent of any thermally activated free radical initiator.
[0081] The absence, presence and amount of free radical initiators (heat activated or radiation activated) in the fully crosslinked fluorinated ionomers of the coating of the microporous membrane composite can be determined by quantitative chemical analysis methods. One such method is nuclear magnetic resonance (NMR) analysis. See Figure 3 Other quantitative chemical analysis methods may also be applicable.
[0082] The exemplary method is shown in Figure 1 The exemplary method can be carried out on a continuous coating line 100, wherein rolls (104) of a continuous length of microporous membrane support 102 are aligned and unrolled, thereby supplying a continuous moving web of support 102 to the coating line 100. Downstream of the rolls 104 are a coater 110 and an electromagnetic radiation source 120. Downstream of the source 120 can be various subsequent optional processing devices 130, 140, 150 and 160.
[0083] In use, the web of carrier 102 is unwound from roller 104 and fed to coater 110, which applies a coating composition (not shown) to the surface of carrier 102 as carrier 102 is continuously moved through coater 110. Coater 110 can be of any suitable type, such as a spray coater, dip coater, curtain coater, optionally using mechanical devices, such as rollers or extrusion rods, which completely immerse the coating composition in the holes of carrier 102 so as to evenly coat the entire surface of carrier 102. A particularly suitable type of coater 110 can be a bath containing a certain volume of coating solution in a container. Carrier 102 can be continuously moved through the volume of coating composition contained in the bath and immersed in the volume to impregnate and evenly coat the entire surface of the porous carrier. The liquid composition in coater 110 can be maintained at a temperature in the range of about 19 to about 26 degrees Celsius.
[0084] After the coating composition has been applied to the surface of the microporous membrane support 102, the resulting support ("coated support") can be passed through electromagnetic radiation so that the fluorinated ionomer of the coating composition becomes crosslinked (i.e., "fully crosslinked") by exposure to the radiation. The coated support 102 moves through the coater 110 in a continuous manner and then passes through electromagnetic radiation 106 emitted by the electromagnetic radiation source 120. The resulting coated support includes a coating of fully crosslinked fluorinated ionomer.
[0085] After the cross-linking step, subsequent steps of treating the coated support may include removing unreacted or excess components from the coating composition remaining on the surface of the support 102, which may be performed by an extractor 130 containing a solvent (e.g., isopropyl alcohol). Subsequently, the solvent may be removed from the remaining coating of the coated support, for example, by using a dryer 140 at an elevated temperature.
[0086] After drying the coating, the coated support can be mechanically converted to a filter membrane, for example, by folding or pleating the dried coated support to form a pleated filter membrane, shown by converter 150. The pleated filter can then be incorporated into a filter device and then chemically treated to convert the functional groups of the fully cross-linked fluorinated ionomer that can be converted to hydrophilic groups into hydrophilic groups, which is shown to occur using apparatus 160 (which can be a single apparatus or multiple apparatuses).
[0087] The described microporous membrane composite can be used as a component of a filter device, which includes various filter structures, such as a support, an outer cylindrical shell or "cage", a frame, an inner cylindrical support or "core", as each configuration in known filter devices. The microporous membrane composite can be folded in a layered configuration with one or more support layers or nets, and potted with a cage, a support and two end cap structures to form a filter cartridge. The cartridge can be of a type that can be replaced within a filter housing, or can be securely bonded to the filter housing.
[0088] Still refer to Figure 1 In the exemplary systems and methods, during all steps, the temperature of the microporous membrane support 102 can be maintained at a temperature that does not cause degradation of the support, such as no more than 170, 150, 120, or 100 degrees Celsius.
[0089] In an exemplary method of preparing a composite, the coating composition can be applied to a microporous membrane support by contacting the coating composition to be applied with the "fluid-contacting surface" (including the outer surface and the inner pore surface) of the membrane support. Preferably, the coating composition can be applied to the support in a manner such that the coating composition contacts all or substantially all of the surface of the support to uniformly coat the entire surface of the support.
[0090] The exemplary method 200 Figure 2 Schematically shown as a block diagram. As shown, a coating operation (210) is used to apply a coating composition as described herein to a microporous membrane carrier. The coating composition can be coated using any effective method and equipment, such as any one or more mechanical coating and dipping techniques for coating the external and internal pore surfaces of the microporous membrane carrier. The coating operation can be performed in a batch or semi-batch method, but preferably the coating composition is applied to the moving net of the microporous membrane carrier by being performed in a continuous manner. Effective techniques used alone or in combination may include: spraying, roller coating, and immersion of the moving net of the membrane carrier through a bath of the coating composition continuously. In some examples of the method and the microporous membrane carrier, the carrier can be patterned by shielding so that the unshielded portion of the microporous membrane carrier is coated with the coating composition, while the shielded portion of the carrier remains uncoated.
[0091] The coating operation 210 (comprising the specific step of applying the coating composition to the film carrier) can be carried out under any applicable conditions and temperature, and the temperature of the coating composition is usually within the range of ambient temperature, for example, below 40 degrees Celsius or below 30 or 25 degrees Celsius. During the continuous coating operation, especially after the coating composition is applied to the carrier in operation 210, and before the subsequent crosslinking operation 214, it is undesirable to evaporate the solvent from the coating composition or dry the coating composition. In order to prevent the solvent from evaporating from the coating composition present on the carrier, and in order to prevent the coating composition present on the carrier from being dried, it is preferably possible to avoid the temperature increase of the coating composition and the carrier. In addition, the solvent of the coating composition with relatively high boiling point, relatively low vapor pressure or both can be selected.
[0092] In cross-linking operation 214, the coated carrier can be placed between radiation transparent films for adding carriers, and the combination can be passed through electromagnetic radiation, which will cause the components of the fluorinated ion polymer in the coating composition to become cross-linked, i.e., "fully cross-linked". The coated carrier can be continuously passed through a chamber irradiated with electromagnetic radiation (e.g., ultraviolet radiation) of a wavelength and amount that causes the fluorinated ion polymer contained in the coating composition to undergo the desired cross-linking. Cross-linking operation 214 can be performed under any applicable conditions and temperatures. To avoid thermal degradation of temperature-sensitive carriers, if used, the interior of the cross-linking chamber ("UV chamber") can be maintained at a temperature that does not allow the carrier to reach a temperature above 170, 150, or 120 degrees Celsius.
[0093] After exposing the fluorinated ionomer to radiation to fully crosslink, the coated support can be subjected to subsequent steps to convert the coated support into a filter membrane (composite) comprising a dried coating having fully crosslinked fluorinated ionomer, wherein the fluorinated ionomer contains hydrophilic groups that allow the membrane composite to exhibit the desired wetting (with methanol and water) and non-dewetting properties.
[0094] As an example of a suitable subsequent step, a coated support having a fully crosslinked fluorinated ionomer on its surface can be treated by one or more chemical extraction steps 220 to remove unreacted, excess chemical components from the fully crosslinked coating composition present at the support surface. The extraction can be performed in a single step or in a series of two or more steps using a liquid, such as water (e.g., deionized water), an organic solvent (e.g., isopropanol), or a combination of these, each step can use the same or different liquid (e.g., solvent or water). The extraction step can be performed at ambient temperature, such as below 40, 30, or 25 degrees Celsius. The liquid can be contacted with the support by spraying, by immersing the support in the liquid, and optionally mechanically agitated, such as by using pressure, such as from a roller, a scraper, etc. In fact, with one or more extraction steps, most of the excess components of the coating composition can be removed from the surface of the coated support.
[0095] After the extraction step (e.g., 220), the coated support can be dried to remove solvent from the surface and the cross-linked fluorinated ionomer coating. The drying step (224) can be performed by exposing the coated support (after extraction) to an elevated temperature for an amount of time sufficient to remove residual solvent, such as by passing the coated support through an oven or a heated chamber containing a heated environment. To avoid thermal degradation of temperature-sensitive support, if used, the temperature of the heated environment can be within a range that does not allow the support to reach a temperature at which thermal degradation will occur as the support moves through the heated environment, for example, the environment can be at a temperature not exceeding 170, 150, or 120 degrees Celsius.
[0096] In the conversion and device fabrication step 230, the dried coated membrane can be processed by folding, cutting, pleating, etc. In this step, the coated support contains a fully cross-linked fluorinated ion polymer, which includes functional groups that can be chemically converted into hydrophilic groups, such as: -SO2F, -COOR, -COF, or a combination of these, where R is a C1 to C20 alkyl or a C6 to C20 aryl. These groups remain as part of the fluorinated ion polymer and can be converted into hydrophilic groups as needed. The conversion operation 230 can produce individual filter membranes from the coated support, and each individual membrane can be incorporated into a single filtration product, such as a filter cartridge or a filter housing. The conversion operation can also include assembling the coated support into a filter device, such as a filter cartridge or a filter housing.
[0097] According to exemplary method 200, after the coated support is first converted to a folded or pleated coated membrane form, and after the converted (e.g., pleated) coated support is incorporated into a filter device (e.g., a filter cartridge or filter housing), the functional groups of the fluorinated ion polymer that can be chemically converted to hydrophilic groups can be converted to hydrophilic groups.
[0098] The first step of chemically converting the functional groups to hydrophilic groups can be to wet or "pre-wet" the coated support via a pre-wetting operation 234. To perform the pre-wetting step, a liquid containing a solvent (e.g., IPA) or water or both can be passed through the device and through the membrane, for example, under ambient conditions.
[0099] In a subsequent hydrolysis step 240, a base, such as ammonium hydroxide or potassium hydroxide, may be maintained in contact with the membrane, for example, at ambient temperature, for an amount of time sufficient to chemically convert the functional groups to counter ions including potassium or -NH4 ions. The device may then be rinsed with water, 224, to remove the ammonium hydroxide or potassium hydroxide. The membrane is then contacted with an acid, such as hydrochloric acid (HCl), 250, to convert the functional groups to hydrophilic (acid) groups. The coated support is subjected to a final hot water rinse 254.
[0100] During all steps of exemplary method 200, the temperature of the microporous membrane support may be maintained below a temperature at which the support may thermally degrade, for example, the temperature of the support may be maintained below 170, 150, 120, or 100 degrees Celsius.
[0101] The membrane composites prepared as described herein may have properties suitable for being considered as "non-dewetting" type of filter membrane composites. The non-dewetting properties of the microporous membrane composites may be determined by heating a sample of the microporous membrane composite that has been in contact with a liquid and wetted in an autoclave to a temperature above the boiling point of the liquid. If the sample is still wet and translucent after autoclaving for a specific amount of time at high temperature, then the sample may be considered to be non-dewetting under those autoclave conditions. For example, when the microporous membrane composite is autoclaved in 135 degrees Celsius water or higher temperature water for 40 minutes to 60 minutes or about 60 minutes, it is considered to be non-dewetting under those conditions.
[0102] Microporous membrane composite samples for autoclave testing can be prepared in the following manner: first wet the sample with a liquid (e.g., a solution containing methanol and water), and then exchange the methanol and aqueous solution with water by rinsing. The water-exchanged sample can be autoclaved in a sealed container with water in an oven. If the microporous membrane support is not coated with enough cross-linked ionic polymer, then subjecting such incompletely coated samples to autoclave treatment in water will cause the incompletely coated samples to dewet and appear opaque after autoclave treatment. Non-dewetting is different from the contact angle measurement of the surface energy of the microporous membrane because non-dewetting refers to the wetting properties of the microporous membrane throughout the thickness and pores of the membrane, which contacts the filtration surface of the liquid, not just the outer surface of the microporous membrane.
[0103] The different wetting properties of the filter membrane composite are the ability of the composite to become wetted (wet / wetted) by solutions of water and methanol. Although the membrane composite may not be wettable directly with water, the exemplary microporous membrane composite may become wettable by solutions containing methanol and water, that is, become "wettable" by solutions containing methanol and water.
[0104] The term "wettable" is used to refer to a microporous membrane composite in a dry state that readily wets or absorbs a solution containing a combination of methanol and water (e.g., a solution consisting essentially of methanol and water) into substantially all of its coated microporous structure within 5 seconds without the use of heat, pressure, mechanical energy, surfactants or other pre-wetting agents.
[0105] Even though the completely cross-linked fluorinated ionomer coating layer formed at the composite surface has a hydrophilic group and the composite is non-dewetting after autoclaving with water, the microporous membrane composite of the present specification may not necessarily be directly wettable with water.
[0106] Wettability can be measured by placing a single drop of methanol and water solution directly on a portion of the microporous membrane composite sample at a height of about 5 cm or less. The time for the drop to penetrate the sample hole is measured. If the drop penetrates the sample hole within 5 seconds and the sample is transparent, the sample is considered wettable by the methanol and water solution drop. If the small drop does not penetrate the microporous membrane composite sample, then the sample is tested again using a methanol and water solution containing a higher weight percentage of methanol.
[0107] The exemplary microporous membrane composite of this specification can be wetted with methanol and aqueous solution containing 95 weight percent or less methanol, for example, by containing 95, 92, 90, 87, 85, 82, 80, 77, 75, 72, 50, 30 or 20 weight percent methanol and the rest being methanol and aqueous solution of water. The microporous membrane composite that can be wetted with the solution of methanol containing the lower limit of these amounts (i.e. containing a lower relative amount of methanol) has a relatively high surface energy and has a high resistance to dewetting. In some instances, the described microporous membrane composite can be wetted with methanol / water containing less than 10 or 5 weight percent or methanol and aqueous solution containing pure water (99 or 100 percent water).
[0108] The described microporous membrane composites that can be wetted with these solutions containing methanol and water can be used in aqueous filtration applications, where an aqueous liquid flows through the membrane without the membrane becoming dewetted. "Aqueous liquid" is a liquid that contains a certain amount of water, and includes aqueous liquids known and used in the semiconductor industry, such as SC1 or SC2 cleaning baths; concentrated sulfuric acid with or without an oxidizing agent (such as hydrogen peroxide or ozone); other water-based liquids that need to be filtered, such as aqueous salt, base or acid solutions (buffered oxide etching).
[0109] In terms of surface tension, at least generally, a microporous membrane composite having a surface energy of 25 dynes / cm or greater can be wetted with a solution containing 80 weight percent methanol / water; a microporous membrane composite having a surface energy of 40 dynes / cm or greater can be wetted with a solution containing 30 weight percent methanol / water; a microporous membrane composite having a surface energy of 50 dynes / cm or greater can be wetted with a solution containing 15 weight percent methanol. Exemplary microporous membrane composites of the present specification can have a surface energy of at least 25 dynes / cm, or at least 27, 30, 32, 35, 37, 40, 45, 50, 55, 60, 65, 70, or 72 dynes / cm (the membrane can be wetted with 100 percent deionized water and 0 percent methanol).
[0110] The fully cross-linked fluorinated ionomer coating on the microporous membrane support prevents the membrane from dewetting during exposure of the microporous membrane composite to a gas such as air, as long as the microporous membrane composite is not exposed for a period long enough to cause the microporous membrane composite to dry. During use in a filtration process, the filter can be exposed to air under a small pressure difference across the filter, such as during displacement of the filtered liquid. In addition, the multi-type microporous membrane composites disclosed in the present invention are particularly suitable for filtering chemically active aqueous liquids, such as acids or bases, including those that may contain gas-generating oxidants or liquids containing high concentrations of dissolved gases. In these cases, the microporous membrane support and the cross-linked ionomer composition are both resistant to chemical degradation, do not exhibit excessive flow loss, and provide a non-dewetting microporous membrane composite.
[0111] The present disclosure will be further described in conjunction with the following non-limiting examples.
[0112] Example 1:
[0113] The porous membrane composite is prepared according to this specification, and its filtration, wettability, flow and other performance and physical properties are tested. Examples are listed in Tables 1 to 4 below. Specifically, the data in Table 1 show that UV curing works on a variety of polymer membranes including heat-stable membranes (PTFE) and heat-sensitive membranes (UPE and PPSU) without the use of free radical initiators. Table 1 also shows that the cross-linked coating increases the surface hydrophilicity of the membrane, which is demonstrated by the lower methanol concentration required to wet the surface of the membrane. The data in Table 2 show that UV curing also works when including radiation-activated free radical initiators (such as Irgacure). Table 2 also shows that the cross-linked coating increases the surface hydrophilicity of the membrane, which is demonstrated by the lower methanol concentration required to wet the surface of the membrane. The data in Tables 3 and 4 show that there is no coating loss when cross-linking is performed only by UV compared to including radiation-activated free radical initiators, such as Irgacure or Na2SO3.
[0114] The membrane IPA flow time as reported herein is determined by measuring the time required for 500 ml of IPA fluid to pass through a membrane having a 47 mm membrane disk and an effective surface area of 17.35 cm at 14.2 psi and a temperature of 21°C. 2 membrane.
[0115] Dye binding test is determined as follows. Dye binding measures the number of functional groups on the membrane or the amount of charge. Methylene blue dye is used to distinguish the negative charge on the surface of the membrane medium. The dry 25mm disc film cut from the modified membrane sheet is pre-wetted with isopropanol, rinsed with DI water and placed on a 50ml vial containing 0.00075wt% methylene blue dye (Sigma) in DI water. The membrane disc is soaked for 2 hours at room temperature under continuous mixing. The membrane disc is then removed, and the absorbance of the dye solution is measured using a Cary spectrophotometer (Agilent Technologies) operating at 606nm, and compared with the absorbance of the starting solution (before the membrane is soaked). The dye is cationic in nature and is bound to a negatively charged membrane to produce a membrane with the dye binding power shown in Table 1 to Table 4. In contrast, unmodified membranes typically show less than 0.3μg / cm 2 Dye binding capacity. Use Figure 4 The slope of the calibration curve depicted in was used to convert the absorbance data of the dye solution before and after immersion of the membrane into wt% of dye, which was then converted into the mass of dye bound per unit area of the membrane. Figure 4The calibration curve shown (y=1760.7×) demonstrates the absorbance of four methylene blue dye solutions with known concentrations measured using a Cary spectrophotometer operating at a wavelength of 660 nm.
[0116] The stability (percent coating loss) as shown in Table 3 was measured as follows: a sample of the modified / coated microporous membrane having a diameter of 47 mm was mounted on a plate having an area of approximately 17.4 cm 2 A mixture of hot isopropyl alcohol (containing 2500 ppm of a fluorosurfactant (from 3M TM Novec TM FC 4432)) was recirculated through the modified microporous membrane sample at a temperature of about 75°C to about 80°C. The surfactant-containing mixture was recirculated for 5 hours from about 250 ml of IPA / fluorosurfactant bath at a flow rate of at least 80 ml / min (depending on the pore size, the flow rate can be in the range of about 80 ml / min to about 120 ml / min). Some bath volume loss occurred due to evaporation and was about 12% in 5 hours. After flowing through the hot IPA / fluorosurfactant, the coated microporous membrane sample was washed with IPA and dried. Dye binding measurements were completed after the sample was exposed to hot IPA FS for 5 hours, and the data were compared with the modified / coated control.
[0117] The "wettability" test can be used to characterize the surface energy of a microporous membrane composite. The liquid composition used to wet the surface of the microporous membrane composite is related to the surface energy (dynes / cm) of the microporous membrane composite. For testing, liquid solutions of various weight percentages of methanol and water were prepared. A drop of the liquid solution was applied to a sample of the modified / coated microporous membrane composite. If the test sample film changes from opaque to translucent in 5 seconds or less, indicating that the film is wetted with the MeOH / water solution, then it is considered that the composite can be wetted with the solution. If the microporous membrane composite sample is not wetted, then a solution containing more MeOH is used. If wetting occurs, then a solution containing less MeOH is used. Sample microporous membrane composites are evaluated using various solutions containing methanol and water; the weight percentage of methanol in the solution that wets the sample is reported.
[0118] Porosimetric Bubble Point (“HFE Average BP”)
[0119] Porosity Determination Bubble Point ("HFE Average BP" in the table below) Test Method measures the pressure required to push air through the wet pores of a porous membrane. The bubble point test is a well-known method for determining the pore size of a membrane.
[0120] The examples describe the Porosimetry Bubble Point Test method for measuring the pressure required to push air through the wet pores of a membrane.
[0121] The test is carried out by installing the 47mm dish of the dry film sample in the bracket. The design of the bracket allows the operator to place a small volume of liquid on the upstream side of the film. The dry airflow rate of the film is measured by first increasing the air pressure on the upstream side of the film to 160psi. The pressure is then released back to atmospheric pressure and a small volume of ethoxy-nonafluorobutane (HFE7200, which can be obtained from 3M Company (3M Specialty Materials, St.Paul, Minnesota, USA) in St. Paul, Minnesota, USA) is placed on the upstream side of the film to wet the film. The wet airflow rate is then measured by increasing the pressure to 160psi again. The bubble point of the film is measured according to the pressure required to displace HFE from the holes of the HFE-wetted film. The critical pressure point is defined as the pressure at which the first nonlinear increase in the wet airflow is detected by the flow meter.
[0122] The HFE average BP of the membrane of the present specification containing the crosslinked fluorinated ionomer coating is about equal to the HFE average BP of the starting (uncoated) membrane, for example, the difference from the starting membrane is no more than 1 or 2 psi. Examples of a range of HFE average bubble points of the membranes produced by the methods described herein are below 100 psi, for example, 25 psi to about 90 psi, as shown in Table 1.
[0123] Table 1
[0124]
[0125] Table 2
[0126]
[0127] Table 3. Coating stability in hot IPA / 2500 ppm fluorinated surfactant. Percent coating loss after 5 hours of flow through recirculation.
[0128]
[0129] Table 4
[0130]
[0131] Example 2:
[0132] refer to Figure 3 , depicts NMR data obtained for three different cross-linked fluorinated ionomers prepared from different liquid coating compositions.
[0133] Figure 3, the top line labeled "Luperox 101" (di-tert-butyl perbenzoate) is a reference line for Luperox 101 thermally activated free radical initiator. The middle line labeled "Present Disclosure" is data obtained for crosslinked fluorinated ionomers prepared from liquid coating compositions disclosed herein, which do not contain any Luperox 101 or other thermally activated free radical initiators, and are crosslinked by exposing the liquid coating compositions to ultraviolet radiation to initiate a crosslinking reaction. The bottom line labeled "Comparative Example" is data obtained for crosslinked fluorinated ionomers prepared from liquid coating compositions containing Luperox 101 according to Example 6 of U.S. Patent No. 9,359,480, which is incorporated herein by reference in its entirety, and are crosslinked by exposing the liquid coating compositions to elevated temperatures to initiate a crosslinking reaction.
[0134] Two different examples, "the present disclosure" and "the comparative example", were prepared as follows:
[0135] The surface-modified PTFE membrane using the above liquid composition was immersed in acetone at 25° C. (about 5 wt %) for 4 days; and
[0136] The extracted acetone was evaporated and the residue was redissolved in acetone (D6) and the sample was tested by NMR.
[0137] The data from the samples are Figure 3 Generally speaking, Figure 3 Shows that if the molecule is present in a cross-linked fluorinated ionomer coating, then free radical molecules such as Luperox 101 can be detected by using NMR analysis. The top line shows peaks a and b, which are characteristic of Luperox 101 free radical initiator molecules. The second line shows that both peaks at a and b, indicating Luperox 101 molecules, are present in the "Comparative Example" sample. The third line shows that the two peaks at a and b, which are characteristic of Luperox 101 molecules, are not present in the "Disclosure" sample. This data illustrates that NMR analysis can be used to determine whether a thermally activated free radical initiator (such as Luperox 101) is present in a cross-linked fluorinated ionomer coating.
[0138] aspect:
[0139] In a first aspect, a microporous membrane composite comprises a microporous membrane support; and a hydrophilic cross-linked fluorinated ion polymer coating on the surface of the microporous membrane support, the cross-linked fluorinated ion polymer comprising: a fluorinated polymer backbone and hydrophilic groups attached to the fluorinated backbone, wherein the hydrophilic groups comprise groups selected from -SO3H, -COOH and PO3H, wherein the cross-linked coating does not contain a thermally activated free radical initiator.
[0140] In a second aspect according to the first aspect, the crosslinked coating contains a UV activated free radical initiator.
[0141] In a third aspect according to any of the preceding aspects, the microporous membrane support comprises a polymer selected from ultra-high molecular weight polyethylene, polyvinylidene fluoride and polyphenylene sulfone.
[0142] In a fourth aspect according to any preceding aspect, the hydrophilic groups are present on the cross-linked fluorinated ionomer in an equivalent amount ranging from 380 to 620 grams per equivalent of hydrophilic groups.
[0143] According to a fifth aspect of any preceding aspect, it has a dye binding capacity of at least 5 μg / cm2.
[0144] According to a sixth aspect of any preceding aspect, it has a wettability (CH3 / H2O mixture) of less than 92 weight percent CH3.
[0145] According to the seventh aspect of any of the preceding aspects, at room temperature at 14.2psi / 500ml / 17.35cm 2 The isopropanol flow time under 100 μl / min was less than 4092 seconds.
[0146] According to an eighth aspect of any preceding aspect, the microporous membrane has a flow loss of 80% or less compared to an uncoated microporous membrane support when measured using 500 ml of isopropanol at a pressure of 14.2 psi.
[0147] According to a ninth aspect of any preceding aspect, it has a surface energy of at least 25 dynes / cm.
[0148] In a tenth aspect according to any of the preceding aspects, the microporous membrane comprises a polymer selected from the group consisting of fluoropolymers, polysulfones, nylons, polyacrylonitrile, polyethylene, ultra-high molecular weight polyethylene, polyvinylidene fluoride, and polyphenylene sulfone.
[0149] In an eleventh aspect, a filter comprises the microporous membrane composite according to any of the preceding aspects.
[0150] In a twelfth aspect, a method for preparing a microporous membrane composite, the microporous membrane composite comprising a microporous membrane support and a cross-linked fluorinated ion polymer coating on the surface of the microporous membrane support, the method comprising: a) coating the microporous membrane with a liquid coating composition, the liquid coating composition comprising a fluorinated solvent and a fluorinated ion polymer dissolved or dispersed therein, the fluorinated ion polymer derived from copolymerized reactive units, the reactive units comprising: i) a fluorinated monomer comprising a fluorinated group and ethylenic unsaturation; ii) a fluorinated monomer comprising ethylenic unsaturation and a functional group that can be converted into a hydrophilic group; iii) a fluorinated diene monomer, and iv) a fluorinated bromo-alkyl or iodo-alkyl chain transfer agent; and b) exposing the coated fluorinated ion polymer to electromagnetic radiation so that the reactive units react to form a cross-linked fluorinated ion polymer.
[0151] In the thirteenth aspect according to the twelfth aspect, the fluorinated ion polymer further comprises one or more iodine and bromine atoms at terminal positions, wherein at least 90% by weight of the fluorinated ion polymer has a particle size of less than 200 nanometers, and wherein the fluorinated ion polymer is derived from copolymerized reactive units, the reactive units comprising: i) a fluorinated monomer comprising a fluorinated group and ethylenic unsaturation; ii) a fluorinated monomer comprising ethylenic unsaturation and a functional group that can be converted into a hydrophilic group; iii) a diene monomer selected from formula (OF-1), (OF-2), (OF-3), wherein: (OF-1) has the following formula
[0152]
[0153] wherein j is an integer between 2 and 10, preferably between 4 and 8, and R1, R2, R3, R4, which are the same or different from each other, are H, F or C1 to C5 alkyl or (per)fluoroalkyl; (OF2) has the following formula
[0154]
[0155] wherein each A is independently selected from F, Cl and H; each B is independently selected from F, Cl, H and ORB, wherein RB is a branched or straight chain alkyl group, which may be partially, substantially or fully fluorinated or chlorinated; E is a divalent group having 2 to 10 carbon atoms, which is optionally fluorinated and may include an ether bond; (OF-3) has the following formula:
[0156]
[0157] wherein E, A and B have the same meanings as defined above; R5, R6, R7 are each independently H, F or C1-5 alkyl or (per)fluoroalkyl; and iv) formula R f (I) x (Br)y A fluorinated chain transfer agent, wherein R f is a fluoroalkyl group or a (per)fluoroalkyl group or a (per)fluorochloroalkyl group having 1 to 10 carbon atoms, and wherein x and y are integers of 0 to 2, wherein 1≤x+y≤2.
[0158] In a fourteenth aspect according to the twelfth or thirteenth aspect, the microporous membrane comprises a polymer selected from the group consisting of fluoropolymers, polysulfones, nylons, polyacrylonitrile, polyethylene, ultra-high molecular weight polyethylene, polyvinylidene fluoride, and polyphenylene sulfone.
[0159] In a fifteenth aspect according to any one of the twelfth to fourteenth aspects, the fluorinated monomer comprising a fluorinated group and ethylenic unsaturation comprises tetrafluoroethylene.
[0160] In the sixteenth aspect according to any one of the twelfth to fifteenth aspects, the functional group that can be converted into a hydrophilic group is selected from the group consisting of: -SO2F, -COOR, -COF, and combinations of these groups, wherein R is a C1 to C20 alkyl group or a C6 to C20 aryl group.
[0161] In the seventeenth aspect as described in any one of the twelfth to sixteenth aspects, it further comprises: continuously applying the liquid coating composition to a moving microporous membrane carrier, and continuously curing the liquid coating composition applied to the microporous membrane carrier by subjecting the moving microporous membrane carrier and the applied liquid coating composition to electromagnetic radiation.
[0162] In an eighteenth aspect according to any one of the twelfth to seventeenth aspects, the liquid coating composition does not contain a thermally activated free radical initiator.
[0163] In a nineteenth aspect according to any one of the twelfth to eighteenth aspects, the liquid coating composition does not contain a free radical initiator.
[0164] In the twentieth aspect according to any one of the twelfth to nineteenth aspects, the liquid coating composition contains a radiation activated free radical initiator
[0165] The twenty-first aspect according to any one of the twelfth to twentieth aspects, further comprising, after exposing the coated fluorinated ionic polymer to electromagnetic radiation to react the reactive units to form a cross-linked fluorinated ionic polymer, contacting the membrane with a solvent to remove unreacted reactive units from the cross-linked fluorinated ionic polymer.
[0166] The twenty-second aspect according to any one of the twelfth to twenty-first aspects, further comprising converting the -SO2F, -COOR or -COF groups into hydrophilic groups by contacting the crosslinked fluorinated ionic polymer sequentially with a base and then with an acid.
[0167] The twenty-third aspect is a microporous membrane composite prepared according to any one of the twelfth to twenty-second aspects.
Claims
1. A microporous membrane composite comprising: a microporous membrane support; and The hydrophilic cross-linked fluorinated ion polymer coating on the surface of the microporous membrane support, the cross-linked fluorinated ion polymer comprising: a fluorinated polymer backbone, and A hydrophilic group connected to the fluorinated backbone, wherein the hydrophilic group comprises a group selected from -SO3H, -COOH and PO3H groups, The crosslinked coating is free of thermally activated free radical initiators.
2. The microporous membrane composite of claim 1, wherein the crosslinked coating contains a UV activated free radical initiator. 3 . The microporous membrane composite according to claim 1 , wherein the microporous membrane support comprises a polymer selected from ultra-high molecular weight polyethylene, polyvinylidene fluoride and polyphenylene sulfone.
4. The microporous membrane composite according to any one of the preceding claims, wherein the hydrophilic groups are present on the cross-linked fluorinated ionomer at an equivalent weight in the range of 380 to 620 g / equivalent hydrophilic groups.
5. A microporous membrane composite according to any one of the preceding claims having a dye binding capacity of at least 5 [mu]g / cm2.
6. The microporous membrane composite of any one of the preceding claims having a (CH3 / H2O mixture) wettability of less than 92 weight percent CH3.
7. A microporous membrane composite according to any one of the preceding claims having a strength of 14.2 psi / 500 ml / 17.35 cm at room temperature. 2 The isopropanol flow time under 100 μl / min was less than 4092 seconds.
8. The microporous membrane composite of any one of the preceding claims, having a flow loss of 80% or less compared to an uncoated microporous membrane support when measured using 500 ml of isopropanol at a pressure of 14.2 psi.
9. The microporous membrane composite according to any one of the preceding claims, having a surface energy of at least 25 dynes / cm.
10. The microporous membrane composite according to any one of the preceding claims, wherein the microporous membrane comprises a polymer selected from the group consisting of fluoropolymers, polysulfones, nylons, polyacrylonitrile, polyethylene, ultra high molecular weight polyethylene, polyvinylidene fluoride, and polyphenylene sulfone.
11. A filter comprising the microporous membrane composite according to any one of the preceding claims.
12. A method for preparing a microporous membrane composite, the microporous membrane composite comprising a microporous membrane support and a cross-linked fluorinated ionomer coating on the surface of the microporous membrane support, the method comprising: a) coating the microporous membrane with a liquid coating composition comprising a fluorinated solvent and a fluorinated ionic polymer dissolved or dispersed therein, the fluorinated ionic polymer being derived from copolymerized reactive units comprising: i) a fluorinated monomer comprising a fluorinated group and ethylenically unsaturated; ii) a fluorinated monomer comprising ethylenic unsaturation and a functional group that can be converted into a hydrophilic group; iii) a fluorinated diene monomer, and iv) a fluorinated bromo- or iodo-alkyl chain transfer agent, and b) exposing the coated fluorinated ionomer to electromagnetic radiation to react the reactive units to form a crosslinked fluorinated ionomer.
13. The method of claim 12, wherein the fluorinated ionic polymer further comprises one or more iodine and bromine atoms at terminal positions, wherein at least 90% by weight of the fluorinated ionomer has a particle size of less than 200 nanometers, and wherein the fluorinated ionomer is derived from copolymerized reactive units comprising: i) a fluorinated monomer comprising a fluorinated group and ethylenically unsaturated; ii) a fluorinated monomer comprising ethylenic unsaturation and a functional group that can be converted into a hydrophilic group; iii) a diene monomer selected from the group consisting of formula (OF-1), (OF-2), (OF-3), wherein: (OF-1) has the following formula wherein j is an integer between 2 and 10, preferably between 4 and 8, and R1, R2, R3, R4, which are the same or different from each other, are H, F or C1 to C5 alkyl or (per)fluoroalkyl; (OF-2) has the following formula wherein each A is independently selected from F, Cl and H; each B is independently selected from F, Cl, H and ORB, wherein RB is a branched or straight chain alkyl group which may be partially, substantially or fully fluorinated or chlorinated; E is an optionally fluorinated divalent group having 2 to 10 carbon atoms, which may include an ether bond; (OF-3) has the following formula: wherein E, A and B have the same meanings as defined above; R5, R6, R7 are each independently H, F or C1-5 alkyl or (per)fluoroalkyl; and iv) Formula R f (I) x (Br) y A fluorinated chain transfer agent, wherein R f is a fluoroalkyl group or a (per)fluoroalkyl group or a (per)fluorochloroalkyl group having 1 to 10 carbon atoms, and wherein x and y are integers of 0 to 2, wherein 1≤x+y≤2.
14. The method of claim 12 or 13, wherein the microporous membrane comprises a polymer selected from the group consisting of fluoropolymers, polysulfones, nylons, polyacrylonitrile, polyethylene, ultra high molecular weight polyethylene, polyvinylidene fluoride, and polyphenylene sulfone.
15. The method of any one of claims 12 to 14, wherein the fluorinated monomer comprising a fluorinated group and ethylenic unsaturation comprises tetrafluoroethylene.
16. The method according to any one of claims 12 to 15, wherein the functional group that can be converted into a hydrophilic group is selected from the group consisting of: -SO2F, -COOR, -COF, and combinations of these groups, wherein R is a C1 to C20 alkyl group or a C6 to C20 aryl group.
17. The method according to any one of claims 12 to 16, further comprising: continuously applying the liquid coating composition to a moving microporous membrane support, and The liquid coating composition applied to the microporous membrane support is continuously cured by subjecting the moving microporous membrane support and the applied liquid coating composition to electromagnetic radiation.
18. The method of any one of claims 12 to 17, wherein the liquid coating composition is free of thermally activated free radical initiators.
19. The method of any one of claims 12 to 18, wherein the liquid coating composition is free of a free radical initiator.
20. A method according to any one of claims 12 to 18, wherein the liquid coating composition contains a radiation activated free radical initiator.
21. The method of any one of claims 12 to 19, further comprising, after exposing the coated fluorinated ionic polymer to electromagnetic radiation to react the reactive units to form a cross-linked fluorinated ionic polymer, contacting the membrane with a solvent to remove unreacted reactive units from the cross-linked fluorinated ionic polymer.
22. The method of any one of claims 12 to 21, further comprising converting -SO2F, -COOR or -COF groups into hydrophilic groups by contacting the crosslinked fluorinated ionic polymer sequentially with a base and then with an acid.
23. A microporous membrane composite prepared according to any one of claims 12 to 22.
